Epistasis in Neuropsychiatric Disorders. Issue 4 (April 2017) - Webber, Caleb
Abstract : The contribution of epistasis to human disease remains unclear. However, several studies have now identified epistatic interactions between common variants that increase the risk of a neuropsychiatric disorder, while there is growing evidence that genetic interactions contribute to the pathogenicity of rare, multigenic copy-number variants (CNVs) that have been observed in patients. This review discusses the current evidence for epistatic events and genetic interactions in neuropsychiatric disorders, how paradigm shifts in the phenotypic classification of patients would empower the search for epistatic effects, and how network and cellular models might be employed to further elucidate relevant epistatic interactions. Trends: Identifying epistatic interactions through hypothesis-free genome-wide approaches remains challenging and the contribution of epistasis to neuropsychiatric risk remains unclear. Many hypothesis-led studies have shown risk-increasing interactions between common variants. There is also evidence that genetic interactions contribute to the pathogenicity of rare multigenic copy-number variants. Current efforts to reduce the phenotypic heterogeneity within cohorts may help to identify the underlying perturbed molecular networks and thereby aid the identification of interactions between their constituent genes.